EFFECT OF THE TERMAL TREATMENT TEMPERATURE ON THE DURABILITY AND THE CRACKING ACTIVITY OF THE CATALYSTS ON THE BASE OF MODIFIED MONTMORILLONITE - Zakarina N. A.,; Kornaukhova N.A.,; Dalelkhauly O.,; Akurpekova A.K.,; Aituganova Sh.Zh., (Academic Scientific Journal of Chemistry, 2019)
Increase of the durability of granules of Al (2.5) NaHMM +НLаY-catalyst at crush with temperature increase of calcination of catalysts from 500 to 6500C is found. It is noticed that the introduction of zeolite Y in the replaced rare-earth form leads to growth of durability of the granulated catalyst. It is shown that preliminary calcination at 550,6000C of the zeolitecontained catalysts supported on the activated Al-pillared montmorillonite in Na-and CaNa – forms, leads to significant reduction of yields of gasoline on these catalysts that demonstrates that heat treatment of the catalyst increases durability, but does not provide necessary activity of the catalyst in the fuel direction.